The Influence Of Atmosphere On Tropical Cyclone Freddy In The Lesser Sunda Islands - Fadhli Aslama Afghani (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Indonesia frequently experiences atmospheric phenomena form Tropical Cyclone annually due to its geographical location situated in tropical regions. The occurrence of Tropical Cyclones in Indonesia typically lasts from 3 hours to 18 days during February to April. One of the Tropical Cyclones that occurred in Indonesia in 2023 was Tropical Cyclone Freddy. This research aims to elucidate the characteristics of Tropical Cyclone Freddy, atmospheric conditions, and its influence on rainfall in the Lesser Sunda Islands. The data utilized include Himawari-9 satellite imagery in the IR (13) band, NWP, ERA-5 meteorological parameters, and GSMaP with time intervals every 6 hours from 5-7 February 2023. Tropical Cyclone Freddy, formed south of East Nusa Tenggara on February 5, 2023, and continued to develop into a mature form on February 6, 2023, at 12:00 UTC, progressing westward. The factors contributing to the formation of this tropical cyclone include elevated Sea Surface Temperature (SST), the presence of the Intertropical Convergence Zone (ITCZ), and the active phase 4 of the Madden Julian Oscillation (MJO). The closest distance between the location of Tropical Cyclone Freddy's occurrence and the mainland occurred on February 6, 2023, at 18:00, at 187 km off Sumba Island. On the other hand, the impacts of the tropical cyclone on meteorological parameters include the occurrence of updrafts in the Lesser Sunda Islands region and an increase in moisture transport to the north and south. Additionally, Tropical Cyclone Freddy exerts a remote effect on rainfall events in the Lesser Sunda Islands.